Serum zonulin levels in pediatric epilepsy: An exploratory comparison between newly diagnosed and refractory cases - Soylu N.; Yuce S.; İçağasioğlu D. F.; Demirel M.; Selek Ş. (My University, 2026)
Background and objectiveThe etiology of epilepsy remains unidentified in a substantial proportion of cases, and immune-related mechanisms have been proposed as potential contributors. Zonulin, a regulator of intestinal epithelial barrier (IEB) permeability, has been implicated in immune activation; however, its validity as a circulating biomarker remains uncertain. This study aimed to investigate serum zonulin levels and their association with epilepsy in pediatric patients.MethodsIn this cross-sectional study, children aged 2–15 years were categorized into three groups: newly diagnosed epilepsy (n = 59), refractory epilepsy (n = 60), and healthy controls (n = 58). All epilepsy cases had unknown etiology. Serum zonulin levels were measured using ELISA. Additional analyses included outlier exclusion, non-parametric comparisons, and covariate-adjusted regression.ResultsSerum zonulin levels were higher in newly diagnosed epilepsy and lower in refractory epilepsy compared with controls. However, after covariate adjustment, the difference between newly diagnosed epilepsy and controls was attenuated, whereas refractory epilepsy remained significantly associated with lower zonulin levels. Notably, the observed opposite trends between groups could not be explained based on the available data. Sensitivity analyses yielded consistent results.ConclusionSerum zonulin levels may differ according to epilepsy status; however, the direction of this relationship varies across disease stages and remains unclear. Given the cross-sectional design, the limitations of zonulin as a biomarker, and potential unmeasured confounders, these findings should be interpreted cautiously as exploratory and hypothesis-generating.
Keywords: Tıp; Kimya; Analitik Kimya; Kromatografi; Kütle Spektroskopisi; Spektroskopik Yöntemler; Sağlık Bilimleri; Temel Tıp Bilimleri; Biyokimya; Temel Bilimler; Medicine; Chemistry; Analytical Chemistry; Chromatographic Analysis; Mass Spectroscopy; Spectroscopical Methods; Health Sciences; Fundamental Medical Sciences; Biochemistry; Natural Sciences; Klinik Tıp (Med); Temel Bilimler (Sci); Yaşam Bilimleri (Life); Klinik Tıp; Biyoloji ve Biyokimya; Doğa Bilimleri Genel; Tıp Genel & Dahili; Çok Disiplinli Bilimler; Kimya Analitik; Clinical Medicine (Med); Natural Sciences (Sci); Life Sciences (Life); Clinical Medicine; Biology & Biochemistry; Natural Sciences General; Medicine General & Internal; Multidisciplinary Sciences; Chemistry Analytical; Genel Sağlık Meslekleri; Patofizyoloji; Temel Bilgi ve Beceriler; Değerlendirme ve Teşhis; Dahiliye; Aile Sağlığı; Biyokimya (tıbbi); Tıp (çeşitli); Genel Tıp; Kimya (çeşitli); Genel Kimya; Filtrasyon ve Ayırma; Multidisipliner; Fizik Bilimleri; General Health Professions; Pathophysiology; Fundamentals and Skills; Assessment and Diagnosis; Internal Medicine; Family Practice; Biochemistry (medical); Medicine (miscellaneous); General Medicine; Chemistry (miscellaneous); General Chemistry; Filtration and Separation; Multidisciplinary; Physical Sciences